Automatic preimage attack framework on Ascon using a linearize-and-guess approach - Li, Huina (2023)
Ascon is the final winner of the lightweight cryptography standardization competition (2018 − 2023). In this paper, we focus on preimage attacks against round-reduced Ascon. The preimage attack framework, utilizing the linear structure with the allocating model, was initially proposed by Guo et al. at ASIACRYPT 2016 and subsequently improved by Li et al. at EUROCRYPT 2019, demonstrating high effectiveness in breaking the preimage resistance of Keccak. In this paper, we extend this preimage attack framework to Ascon from two aspects. Firstly, we propose a linearize-and-guess approach by analyzing the algebraic properties of the Ascon permutation. As a result, the complexity of finding a preimage for 2-round Ascon-Xof with a 64-bit hash value can be significantly reduced from 2^39 guesses to 2^27.56 guesses. To support the effectiveness of our approach, we find an actual preimage of all ‘0’ hash in practical time. Secondly, we develop a SAT-based automatic preimage attack framework using the linearize-and-guess approach, which is efficient to search for the optimal structures exhaustively. Consequently, we present the best theoretical preimage attacks on 3-round and 4-round Ascon-Xof so far.